Legal Ideas Related to Protecting The Rights of Indonesian Migrant Workers with Morality and Dignity - Arista, Windi; Rusmini; Zuhir, Mada Apriandi (Faculty of Law, Universitas Pekalongan, 2024)
Indonesian migrant workers face various challenges related to the protection of their human rights, both in their countries of origin and destination. Protection of their rights is often ignored or violated, leading to inhumane and degrading treatment. Through a normative research method with a statutory and conceptual approach, this article analyzes the applicable national and international legal framework, including the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families and the Indonesian Migrant Workers Protection Act.The results show that despite the existence of various legal instruments designed to protect migrant workers, their implementation is often hampered by various factors, such as a lack of inter-agency coordination, weak law enforcement, and migrant workers' limited access to justice. This article proposes several recommendations, including the need for increased awareness and legal education for migrant workers, strengthening the role of the state in protecting their rights, as well as the establishment of a specialized institution responsible for ensuring that the protection of migrant workers' rights is implemented with morality and respect for their dignity as human beings.